Медіа-реальність як сучасний соціокультурний простір - Москвич, Ольга Дмитрівна; Москвич, Ольга Дмитриевна; Moskvych, Olha D. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Медіа-реальність есплікується як специфічна структура соціокультурної реальності з технологічною детермінованістю; її характерні риси – динамічність інформаційного потоку, візуалізація та віртуалізація соціокультурних феноменів, глобалізація й фрагментарність сприйняття, а також аксіологічна незбалансованість і маніпулятивність. Запропоновано можливі способи розвʼязання актуальних проблем медіа-екології, що виникають унаслідок агресивної медіа-експансії: законодавче втручання та суспільна саморегуляція допустимої міри і якості візуальної інформації, а також підвищення рівня медіа-грамотності реципієнтів. The reality of the media is explicated as a specific structure of socio-cultural reality with technological determination that has its own ontological characteristics. The defining attributes of the reality of media have been outlined, among which the dynamism of the information stream, visualization and virtualization of socio-cultural phenomena, globalization and fragmentariness of perception, as well as axiological disequilibrium and manipulativity are fundamental. When affected by media, socio-cultural connections and paradigms of post-modern identity perplex, as also social, religious, political and cultural priorities are planned. Challenging issues of media ecology which come up under the influence of aggressive media expansion are reviewed, and some possible remedies are suggested, including legislative intermediation and social self-direction of appropriate limit and quality of visual information, along with the stiffening media literacy of the subjects of perception.
Media Reality as a Modern Socio-Cultural Space
Keywords: медіа; медіа-реальність; медіа-екологія; соціокультурний простір; media; media reality; media ecology; socio-cultural space